2001
DOI: 10.1182/blood.v98.6.1752
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a FLT3 internal tandem duplication in patients with acute myeloid leukemia (AML) adds important prognostic information to cytogenetic risk group and response to the first cycle of chemotherapy: analysis of 854 patients from the United Kingdom Medical Research Council AML 10 and 12 trials

Abstract: In acute myeloid leukemia (AML), further prognostic determinants are required in addition to cytogenetics to predict patients at increased risk of relapse. Recent studies have indicated that an internal tandem duplication (ITD) in the FLT3 gene may adversely affect clinical outcome. This study evaluated the impact of a FLT3/ITD mutation on outcome in 854 patients, mostly 60 years of age or younger, treated in the United Kingdom Medical Research Council (MRC) AML trials. An FLT3/ITD mutation was present in 27% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
1,132
19
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,375 publications
(1,222 citation statements)
references
References 18 publications
57
1,132
19
14
Order By: Relevance
“…Many studies indicate that FLT3-ITD confers a poor prognosis in AML patients by increasing relapse risk and reducing survival. [17][18][19][20][21] More recently, increasing evidence suggests that higher FLT3-ITD to wild-type allelic ratios are associated with poor prognosis. 22 In our patients, FLT3 mutation by itself did not impact DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that FLT3-ITD confers a poor prognosis in AML patients by increasing relapse risk and reducing survival. [17][18][19][20][21] More recently, increasing evidence suggests that higher FLT3-ITD to wild-type allelic ratios are associated with poor prognosis. 22 In our patients, FLT3 mutation by itself did not impact DFS.…”
Section: Discussionmentioning
confidence: 99%
“…31 These findings were subsequently confirmed in numerous other trials. [33][34][35][36][37] In general, patients with FLT3-ITD AML achieve complete remission rates comparable to those of patients with wild-type disease, but have significantly higher rates of relapse and shorter durations of disease-free and overall survival (OS).…”
Section: Flt3 As a Prognostic Markermentioning
confidence: 65%
“…[33][34][35][36][37] In general, patients with FLT3-ITD AML achieve complete remission rates comparable to those of patients with wild-type disease, but have significantly higher rates of relapse and shorter durations of disease-free and overall survival (OS). 31,[33][34][35] In the Medical Research Council studies, patients with FLT3-ITD AML had a 74% relapse rate vs 48% for patients with FLT3-wild-type AML. 31 The 5-year OS rate was 32% for patients with FLT3-ITD AML vs 44% for patients with FLT3-wildtype AML; 31 event-free survival was 20 vs 41 weeks, respectively (Po0.00001).…”
Section: Flt3 As a Prognostic Markermentioning
confidence: 99%
See 1 more Smart Citation
“…62 These activating mutations of FLT3R, particularly a homozygous activation, confer a worse outcome. 63,64 Inhibitors of such aberrant activation are undergoing clinical evaluation. 65 Early clinical trials have demonstrated activity of FLT3 inhibitors, particularly in patients who harbor FLT3R mutations in their leukemic blasts.…”
Section: Constitutively Active Kinases As Targets Of Therapymentioning
confidence: 99%